2019
DOI: 10.3390/ijerph16193760
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Ambient Air Pollution on ST-Elevation Myocardial Infarction Events: Are There Potentially Susceptible Groups?

Abstract: Background: Air pollution exposure is associated with greater risk for cardiovascular events. This study aims to examine the effects of increased exposure to short-term air pollutants on ST-segment elevation myocardial infarction (STEMI) and determine the susceptible groups. Methods: Data on particulate matter PM2.5 and PM10 and other air pollutants, measured at each of the 11 air-quality monitoring stations in Kaohsiung City, were collected between 2011 and 2016. The medical records of non-trauma adult (>17 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 46 publications
3
23
0
3
Order By: Relevance
“…28 Epidemiological studies have shown that participants with hyperlipidemia exposure to PM 2.5 may make them more susceptible to a higher risk of developing CVDs. [29][30][31] Therefore, we need a more thorough understanding of the potential mechanisms in order to develop preventive intervention strategies. Consequently, we use an ApoE −/− mouse model which is a mature animal model of hyperlipidemia.…”
mentioning
confidence: 99%
“…28 Epidemiological studies have shown that participants with hyperlipidemia exposure to PM 2.5 may make them more susceptible to a higher risk of developing CVDs. [29][30][31] Therefore, we need a more thorough understanding of the potential mechanisms in order to develop preventive intervention strategies. Consequently, we use an ApoE −/− mouse model which is a mature animal model of hyperlipidemia.…”
mentioning
confidence: 99%
“…In the current study, we evaluated the short-term effects of PM 10 pollution on the frequency of ACSs treated with PCI. In a Boston study and other studies, a relationship was found between the short-term increase in air pollution (hours) and the increased incidence of ACS rate (Peters et al 2001, Pan et al 2019and Chen et al 2020. The relationship of the extent of air pollution expressed as PM 10 concentration has also been demonstrated in other countries with a warmer climate (Cendon et al 2006).…”
Section: Discussionmentioning
confidence: 66%
“…2b). PM exposure increases the risk for cardiovascular events [5,6] and respiratory disease [3,4,12,14]. Children are highly vulnerable to the adverse effects of air pollution, particularly to respiratory diseases [12].…”
Section: Resultsmentioning
confidence: 99%